Survei Kondisi Fisik dan Kemampuan Teknik Dasar Futsal pada Klub Danutama FC di Kabupaten Karanganyar Tahun 2021 - Adhi Kurniawan; Tommy Soenyoto (Indonesian Journal for Physical Education and Sport, 2023)
The research problem is how the physical condition and basic technical abilities of futsal players on the Danutama Fc team in Karanganyar Regency in 2021. The study aims to determine the physical condition and basic technical abilities of futsal players on the Danutama Fc team in Karanganyar Regency in 2021. The research method uses a test survey and analysis of research data using descriptive percentages. The results showed that: 1) the physical condition of the futsal players for the Danutama Fc team in 2021 was in the very poor category, there were 3 players with very good scores with a percentage (15%), 5 players with good scores with a percentage (25%), 4 players with medium score with percentage (20%), 2 players with less score with percentage (10%), 6 players with less score with percentage (30%). 2) The basic technical ability of the Danutama Fc futsal team in Karanganyar Regency in 2021 in the medium category, there are 0 players with very good scores with percentages (0%), 6 players with good scores with percentages (30%), 8 players with moderate scores with percentage (40%), 4 players with less score with percentage (20%), 2 players with less score with percentage (10%). Based on the results of the study, it is recommended that the Danutama Fc futsal team in providing physical condition training and basic techniques need to increase the intensity of the exercise and increase the training load.